2021
DOI: 10.1108/ijdi-11-2020-0260
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing work-related movement during a pandemic. Location analytics and the implications of the digital divide

Abstract: Purpose The purpose of this study is to examine the role of digital infrastructure in supporting compliance with travel restrictions. The purpose of this study is to examine the role of digital infrastructure in supporting compliance with travel restrictions. In response to the COVID-19 pandemic, countries around the world have issued “stay-at-home” orders and curtailed a variety of economic activities. As countries have adopted aggressive policies to limit the spread of COVID-19, varying levels of national in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…However, the firms have figured out how to improve the resilience of their global SC in the face of severe calamities (Ivanov and Das, 2020; Modgil et al , 2021). It has changed typical work-related mobility to digital work (Taylor and Taylor, 2021). Digital evolution has caused local and international pressures on typical business leaders through many restrictions (Ivanov and Dolgui, 2021; Ahmad and John, 2021; Parmata and Chetla, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the firms have figured out how to improve the resilience of their global SC in the face of severe calamities (Ivanov and Das, 2020; Modgil et al , 2021). It has changed typical work-related mobility to digital work (Taylor and Taylor, 2021). Digital evolution has caused local and international pressures on typical business leaders through many restrictions (Ivanov and Dolgui, 2021; Ahmad and John, 2021; Parmata and Chetla, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ivanov and Dolgui (2020), Fierro Hernandez and Haddud (2018) and Kurniawan et al (2017)'s study pointed out that risk management culture positively facilitates supply chain visibility and supplier development, a common technique in Indonesia firms on supply chain responsiveness. Besides, Taylor and Taylor's (2021) study indicated that advanced digital infrastructure might be better prepared for global nations to adapt the societal disruptions such as the COVID-19 outbreak. Bag et al (2021a) and Saglam et al (2020)'s study findings showed that supply chain responsiveness and resilience, which are risk-mitigating tactics, positively deal with supply chain risk management (SCRM).…”
Section: Key Supply Chain Challenges and Managing The Opportunitiesmentioning
confidence: 99%
“…These new tools, while opening new unprecedented opportunities for many, constituted new barriers for others. Limited and unequal access to digital infrastructures can influence teleworking, e-commerce adoption, distance learning, use of telehealth platforms, and more in general the ability to carry out activities from home thus limiting travels and mobility [24][25][26][27][28][29][30]. However, these factors have not been yet extensively explored via a quantitative data-driven approach.…”
Section: Introductionmentioning
confidence: 99%